Clinical Signs and Blood Variables of Pregnancy Toxemia Goats during Late Gestation and Postpartum - A. A. Affan; A. Salleh; M. Zamri-Saad; A. Jayanegara; H. A. Hassim (Tropical Animal Science Journal, 2022)
Pregnancy toxemia is one of the common metabolic diseases in ruminant, which has caused a huge economic impact on the dairy industry. Thus, this study aimed to describe the clinical and blood changes in pregnant goats following induction of pregnancy toxemia. Twelve pregnant goats were divided into control (n=3) and treatment (n=9) groups. The control was fed a diet with adequate energy while the treatment group was exposed to 50% reduction in the energy intake to induce pregnancy toxemia. Blood samples were collected at weekly intervals for biochemical analyses, which included glucose, beta-hydroxybutyrate (BHBA), free fatty acid (FFA), calcium, sodium, potassium, chloride, cortisol, and insulin. On days 20 (PK20) and 40 (PK40) post-induction, 3 induced and 1 control goat was slaughtered while the remaining 3 induced goats were provided with a normal balanced diet to allow recovery (PKRD). The induction resulted in acute pregnancy toxemia after 20 days with clinical signs including weakness, loss of body condition, and recumbency. At 40 days, chronic pregnancy toxemia resulted in signs such as incoordination and abortion. There was significant (p<0.05) decrease in the glucose, insulin, calcium, and potassium levels in the induced goats while the concentrations of BHBA, FFA, and cortisol were significantly (p<0.05) higher. Furthermore, the blood profiling was significantly (p<0.05) different between the PK20, PK40, and PKRD groups and was strongly associated with the presence of clinical signs and ketone bodies in the urine. The 50% reduction in energy intake resulted in acute pregnancy toxemia after 20 days and chronic pregnancy toxemia after 40 days. In conclusion, serum biochemical profile is a potential biomarker to assess the mild and severe pregnancy toxemia in does during the late gestation and postpartum period through changes in blood profiling.